Psychological Well-Being of Muslim Online Gamers in Malaysia: Are They Mentally Well Enough? Array - Farhana Sabri; Ahmad Yunus (Islamic Guidance and Counseling Journal, 2021)
The psychological well-being of online gamers has gotten more attention as online games have become recognized in the e-sport field. Hence, identifying the psychological status of gamers is essential to ensure their well-being is at optimum, and further interventions can be strategized if needed. The identified psychological profiles include psychological well-being, duration of play, and internet gaming disorder. A total of 221 Muslim online gamers from various e-sport centers and academies in Malaysia participated in this study. The psychological well-being was measured using Psychological Well-Being Scale, while IGD was measured using the Internet Gaming Disorder Scale-Short Form. The results indicated that the frequency of playing online games and daily play duration were associated with gamers' psychological well-being. Furthermore, preoccupation and withdrawal symptoms of gaming disorder were significant in predicting psychological well-being. The importance of this study for Muslim online gamers is to increase their awareness on the continued interweaving of psychological well-being and internet gaming disorder experience, so that early mental distress can be best addressed.